Set of harmonized european standards for proof of competence of cranes – update 2019 - Vöth, S. (Національний технічний університет "Харківський політехнічний інститут", 2019)
With EN 13001-1 ff. a harmonized set of standards for safety of cranes was and is established. Due to harmonization the use of the standards leads to the assumption of conformity with the safety requirements of the machinery directive. A major argument for the application of the standards. The standards comprise new concepts of proof of competence in comparison to previous standards. Keywords of these new concepts are "Classification", "Limit state method", "Mass Distribution Class" and "Partial safety factors". The article gives an overview to EN 13001-1, EN 13001-2, EN 13001-3-1 and EN 13001-3-3. This is the set of standards for the proof of the structural parts and wheel/rail contacts of a crane. The main aspects of the standards are shown and discussed with regard to their impact on calculation.

У статті досліджено проблему гармонізації нормативних документів, спрямованих на забезпечення безпечної експлуатації підйомно-транспортних машин (кранів). На прикладі гармонізації розглянутих стандартів EN 13001-1, EN 13001-2, EN 13001-3-1 та EN 13001-3-3, які містять нові концепції, показано відповідність вимогам безпеки за Директивою ЄС «Машини, механізми та машинне обладнання». Розглянуті ключові концепції: «Класифікація», «Метод граничного стану», «Клас розподілення за масою» та «Коефіцієнт запасу міцності», що використовуються для перевірки придатності конструктивних елементів, колісних і рейкових контактів крана, а також впливають на їх розрахунок.
Комплект гармонізованих європейських стандартів, що регламентують вимоги до кранів – оновлення 2019
Keywords: safety operation; crane contacts; безпечна експлуатація; контакти крана